Image of Surya - Temples of India Project Team (Jio Institute, 2024)
This majestic image of Surya, now in the Akbari Fort and Museum in Ajmer, must have once been placed inside the sanctum of a lost Surya shrine. Coupled with multiple other Surya images at the shrine (Surya, Chhaya, etc.), it suggests the maturity of the Surya tradition at the hill, present there at least from the 8th century CE, much before the emergence of the Harshadeva-Shiva as the royal shrine at the hill. He is holding two fully bloomed-lotuses in either hand. He is flanked on either side by his companions, Danda and Pingala, positioned immediately near his legs, with the pair of the horse-faced Ashvin brothers at the back. On the above register is an elegant pair of bow holders about to unleash the arrow. Surya is wearing the kirita-mukuta, and the radiant halo in the form of a fully bloomed lotus appropriately suits the radiant glow of the Sun God. Surya is wearing the kirita-mukuta, and the radiant halo in the form of a fully bloomed lotus appropriately suits the radiant glow of the Sun God.